Effect of topographical control by a micro-molding process on the activity of human Mesenchymal Stem Cells on alumina ceramics. Issue 1 (December 2015) - Kim, Soo-Yean; Kang, Jong-Ho; Seo, Won-Seon; Lee, Suk-Won; Oh, Nam-Sik; Cho, Hyung-Koun; Lee, Myung-Hyun
Abstract Background Numerous studies have reported that microgrooves on metal and polymer materials can affect cell adhesion, proliferation, differentiation and guidance. However, our knowledge of the cell activity associated with microgrooves on ceramics, such as alumina, zirconia, hydroxyapatite and etc, is very incomplete, owing to difficulties in the engraving of microgrooves on the hard surface of the base material. In this study, microgrooves on alumina were fabricated by a casting process using a polydimethylsiloxane micro-mold. The cell responses of Human Mesenchymal Stem Cells on the alumina microgrooves were then evaluated. Results Microgrooves on an alumina surface by micro-mold casting can enhance the adhesion, differentiation of osteoblasts as well as gene expression related to osteoblast differentiation. The ALP activity and calcium concentration of the cells on alumina microgrooves were increased by more than twice compared to a non-microgrooved alumina surface. Moreover, regarding the osteoblast differentiation of hMSCs, the expression of ALP, RUNX2, OSX, OC and OPN on the microgrooved alumina were all significantly increased by 1.5 ~ 2.5 fold compared with the non-microgrooved alumina. Conclusion Altering the topography on alumina by creating microgrooves using a micro-molding process has an important impact on the behavior of hMSCs, including the adhesion, differentiation of osteoblasts and osteoblast-specific gene expression. The significant increase in hMSC activity is explained by the increasing of material transportation in parallel direction and by the extending of spreading distance in perpendicular direction.